Self‐assembled fullerene (C60)‐pentacene superstructures for photodetectors. (8th March 2021) - Tang, Qin; Zhang, Guangpu; Jiang, Bohong; Ji, Deyang; Kong, Huihui; Riehemann, Kristina; Ji, Qingmin; Fuchs, Harald
Abstract: Fullerene assembling with specific donor molecules would yield multifunctional metamaterials via the collective behavior, wherein linear acenes are widely used as donor molecules to construct the charge‐transfer heterojunction structure with fullerene. However, they are generally prepared by vacuum deposition due to the insoluble property of high‐performance linear acenes molecules in common solvents, which makes the construction of fullerene with insoluble donor molecules still be a big challenge in the solution‐processed method. To this end, chemical modification provides an effective solution‐processed strategy to construct donor and acceptor systems. Here, the C60 ‐pentacene is assembled into controllable flower‐like superstructures by the surface grafting method. It is found that the nanofeatures of the microflowers could be regulated by temperature, resulting in dense‐flakes morphology at room temperature and loose flakes at high temperatures. Furthermore, the dense‐flakes microflowers structures with less mass but better crystalline structure exhibit better optoelectronic properties. Our results reveal an effective control on the nanofeatures of the self‐assembled fullerenes complex superstructures and their role for the optoelectronic performance, which may promote the exploring of fullerene superstructures as photodetectors. Abstract : Nanofeatures of C60 ‐pentacene microflowers could be regulated by temperatures, which shown dense‐flakes morphology at 110°C and loose flakes at room temperature. They also demonstrated different optoelectronic properties indicating a highly effective functional design for fullerene superstructures.